Cytokine and Cancer Biomarkers Detection: The Dawn of Electrochemical Paper-Based Biosensor - Song Wei Loo; Tze-Sian Pui (Sensors, 2020)
Although the established ELISA-based sensing platforms have many benefits, the importance of cytokine and cancer biomarkers detection for point-of-care diagnostics has propelled the search for more specific, sensitive, simple, accessible, yet economical sensor. Paper-based biosensor holds promise for future in-situ applications and can provide rapid analysis and data without the need to conduct in a laboratory. Electrochemical detection plays a vital role in interpreting results obtained from qualitative assessment to quantitative determination. In this review, various factors affecting the design of an electrochemical paper-based biosensor are highlighted and discussed in depth. Different detection methods, along with the latest development in utilizing them in cytokine and cancer biomarkers detection, are reviewed. Lastly, the fabrication of portable electrochemical paper-based biosensor is ideal in deliberating positive societal implications in developing countries with limited resources and accessibility to healthcare services.